Analisis Forensik Aplikasi Dropbox pada Android menggunakan Metode NIJ pada Kasus Penyembunyian Berkas - Saad, Saleh Khalifah; Umar, Rusydi; Fadlil, Abdul (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Smartphones are a testament to the development of digital technology. At this time, the smartphone is also experiencing growth in storage media, one of which is the Cloud storage media. One cloud storage application is the Dropbox Application. The development of cloud storage media does not rule out the possibility of a negative impact on the use or can be used as a medium for crime, such as storing evidence of criminal transactions and cybercrime. This study uses conversation scenarios for application conditions, including data deletion in applications. Data for each experiment will be taken using the National Institute of Justice (NIJ) Method. The method used in dealing with crime with smartphone media evidence is the National Institute of Justice (NIJ) Method. The conclusion of this study is that the use of the National Institute of Justice (NIJ) method ranks the digital forensic stages, starting with identification, collection, examination, analysis, and reporting very well. This method is widely used in handling digital crime cases. The results of the acquisition will then be analyzed by translating the hex codes resulting from the acquisition to produce evidence that can be understood by the judge later.